A Diffusion Theory Perspective on the Adoption of Online Shopping Among Youth in Central Kerala - Thomas K V (International Journal of Innovative Research in Science, Engineering and Technology, 2014)
Internet shopping refers to any form of shopping that take place via the internet. The present study attempts to identify the factors that influence the adoption of online shopping drawing ideas from the diffusion theory. It was found that all the independent variables viz, Voluntariness, Relative advantage, Ease of use, Compatibility, Trial ability, Demonstrability and Image or status s have a positive relationship with the dependent variable, rate of online shopping. However, stepwise regression showed that only two variables can significantly predict the dependent variable, rate online shopping. They are Compatibility and Voluntariness.